Optimization of Cascara Briquettes for Renewable Energy Production through Thermoelectric Generators as an Extension of the RBL-STEM Model in Enhancing Students' Creative Thinking Skills - Nurul Komaria; Nostalgianti Citra Prystiananta (Jurnal Penelitian Pendidikan IPA, 2025)
The global fossil fuel crisis and demand for sustainable renewable energy sources have driven the development of biomass-based alternative fuels. Cascara, a coffee husk by-product with high cellulose content and wide availability, has strong potential for conversion into biomass briquettes; however, improvements in fuel quality and energy conversion efficiency are needed. This study aims to improve the physical, thermal, mechanical, and emission performance of cascara briquettes by varying the composition of cascara leaves, bletong, and Tectona grandis, as well as integrating the optimized briquettes as a heat source in a thermoelectric generator (TEG) system. This study also evaluates the effectiveness of applying a STEM-based Research-Based Learning (RBL-STEM) model in improving students' creative thinking skills. This study was conducted in two stages. The experimental stage used a completely randomized design with ten briquette formulations and tested the calorific value, combustion rate, impact strength, and emissions. The learning stage applied the research results to 35 students using a single-group pretest-posttest design. The data were analyzed using instrument validation, normality tests, correlation analysis, and paired sample t-tests. The best formulation (70:20:10) produced the highest calorific value, while 50:30:20 produced the lowest emissions. The implementation of RBL-STEM significantly improved students' creative thinking performance.